Studies on Pre-cooling of Mango for Extension of Shelf-Life - Khanbarad, Sonali C.; Patil, Nandkishor; Sutar, R. F.; Joshi, D. C. (Journal of Agricultural Engineering, 2014)
A study was undertaken to observe the effect of pre-cooling on extending the shelf life of mango fruit (cv Neelam). Fully matured, good quality mango fruits were subjected to chilled water dipping, hydro-cooling and forced air cooling at 5 and 8 °C, and compared with control treatments. Pre-cooled samples were shifted to three storage environments viz. ambient temperature (30 ± 3 °C), evaporative cooled storage (26 ± 3 °C) and cold store (13 °C at 85 to 90% RH). Results showed that chilled water dipping was the best method with minimum pre-cooling time (26 min at 5 °C). The minimum physiological loss in weight (PLW) (9.98%), TSS (17.90 °Brix), spoilage (10.47%) and maximum firmness (1.4 N) and titrable acidity (0.34%) were obtained for samples pre-cooled by chilled water dipping stored at cold storage. Maximum shelf life of 36 days was obtained for chilled water dipping at 5°C, followed by control (no pre-cooling) samples, 26 days at cold storage and only 10 days at ambient storage condition.